The feasibility of using the Microsoft KinectTM to measure the degree of movements’ precision for affected upper limbs motion of children with hemiplegia in home-based therapy: Feasibility study - Mohammed Elsaeh (Journal of Pure & Applied Sciences, 2020)
Home-based therapy, that base on haptic-virtual games systems, increases the overall time of the therapy for hemiplegic children. Low cost depth sensors might be needed to evaluate the joint coordinates in order to produce movements. In this study, a body modulation and clinically-based angle calculations for random upper limb movements in 3D space have been created and validated. The shoulder joint flexion-extension angle, shoulder abduction-adduction angle, elbow flexion-extension, wrist flexion-extension angle and wrist abduction-adduction angle has been performed by a subject. KinectTM system and the Vicon motion capture system have been used to measure those movements. Results illustrate a clinically acceptable error of these movements and its angles which around 4.9% for shoulder joint, around 3.9% for elbow joint, and around 4.8% for wrist joint for most cases.